If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -1y = 59 Solving 4x + -1y = 59 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'y' to each side of the equation. 4x + -1y + y = 59 + y Combine like terms: -1y + y = 0 4x + 0 = 59 + y 4x = 59 + y Divide each side by '4'. x = 14.75 + 0.25y Simplifying x = 14.75 + 0.25y
| 3x*4(x+10)=620 | | 6x+11=-43-8x | | 3x-7=28-4x | | y=6-5x-3x^2 | | 7+4x=-1+x | | x^3=2.5 | | 4u^2-5u-1=0 | | X/6=10/8 | | Cosx=sin(x+30) | | (2x-15)=(x+5) | | x*2+14x-20=0 | | X*x+X-6=y | | X*x+6-6=y | | 60+60*0+11= | | 3x^2=12x+15 | | z^3+3z+1=0 | | 8x+5+4x-5+x=180 | | 7y+4x=7 | | -23x+27=42x+19 | | 19x+42=18x | | 2px^2-6px+4p=0 | | 5x+42=32 | | 42/28/21 | | 5=8sin(1.06t) | | (46+y)+56+31=180 | | 0.3x+0.6y=15 | | z^2=-5-2i | | -x-3x+7=0 | | 18x+27=14x | | -32a^2-44a+15=0 | | 50x-5=14 | | x^4+6x^3+8x^2+6x+-9=0 |